Chemical Characteristics of Fermented Local Waxy White Corn as an Effort to Improve the Quality of Bose Corn - Maria Susana Medho; Endeyani Vivitrida Mohamad (The University of Lampung, 2024)
Bose waxy corn is limited in storage and of low quality so that need to e improved. This research aims to test the physical and chemical properties of bose waxy corn products modified with tape yeast and to find the right chemical properties of bose waxy corn products modified with tape yeast and to find the right time and amount of tape yeast to improve the quality of bose corn products. The research was carried out experimentally with 2 factors tested, namely faktor I: tape yeast concentration (R): R1= 0.1%, R2= 0.2%, and R3= 0,3%, faktor 2: Fermentation time (F): F1= 12 H, F2 = 24 H, and F3 = 36 h. The results of the research showed that chemically the best modified bose waxy corn was treated with a tape yeast concentration of 0.1% with a fermentation time 24 h (R1F2). The moisture content of modified bose corn was obtained at 9.75%, the lowest pH was 4,5 and the highest total acid was 0.067% can give corn a whiter color and longer shelf life. The R1F2 treatment also produced the highest protein of 9.07%, soluble protein of 0.26%, amylose content of 5.78% and was not significantly different from R2F2. The ash content was higher in the R2F1 treatment, that is 0.57% and not significantly different from R2F2, namely 0.56%. Keywords: Bose corn, Fermentation, Waxy corn, Yeast tape